" Lithofacies and Organic Geochemical Studies of Akinside 1582 Well, Eastern Dahomey Basin Southwestern Nigeria " (2011)
"Subsurface samples from the Akinside 1582 well, located within the eastern Dahomey Basin were evaluated to determine the lithofacies, depositional environment, and hydrocarbon potential of the basin. The sediments within the interval 138-197m consist of limestones, shales, mudstone and glauconite; thus representing sediments belonging to the Ewekoro and Akinbo Formations. The limestones are greyish, highly indurated, partly recrystallised and reveal six microfacies notably biosparite, shelly biomicrite, biomicrite, pel-biosparite, sandy-pelmicrite and sandy-biomicrite. The presence of gastropods, pelecypods, echinoderm, coralline algae, foraminifera and other skeletal debris indicate a shallow marine environment of deposition for the limestone. Total organic carbon (TOC) for the sediments range from 0.10 to 0.58wt% and 0.59 to 0.62wt% for the Ewekoro and Akinbo Formations respectively while soluble organic matter (SOM) are correspondingly 392ppm and 887 to 2472ppm. These suggest a poor through moderate to adequate organic matter. Plot of HI versus Ol indicates Type III and IV kerogens. Tmax value range from 362 to 467°C and cross plot of HI versus Tmax points to mainly immature to early mature sediments. The terpanes and sterane distributions indicate a marginally mature status for the sediments. Pristane/phytane ratio ranges from 0.13 to 0.24 and 1.88 for the Akinbo and Ewekoro Formations respectively, thus indicating both anoxic and oxic conditions of deposition. The abundance of pentacyclic triterpane of oleanane and hopane skeletons and C27 to C29 regular steranes in the bitumen, indicate mixed source rocks (marine and terrestrial) for the sediments. However, ternary plot of C27, C29 and C29 steranes strongly amplify terrestrial organic matter with prospect to generate gas rather than oil in the basin at appropriate maturation. "